2010
DOI: 10.1098/rstb.2010.0148
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phenological mismatches on demography

Abstract: Climate change is altering the phenology of species across the world, but what are the consequences of these phenological changes for the demography and population dynamics of species? Time-sensitive relationships, such as migration, breeding and predation, may be disrupted or altered, which may in turn alter the rates of reproduction and survival, leading some populations to decline and others to increase in abundance. However, finding evidence for disrupted relationships, or lack thereof, and their demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
517
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 543 publications
(546 citation statements)
references
References 94 publications
6
517
0
2
Order By: Relevance
“…In both the bay checkerspot and the winter moth, difficulty in documenting long-term changes in phenological synchrony stems partly from successive groups of researchers having recorded information on phenologies, fitnesses, and so on in different ways that are not strictly comparable. In order to properly record both phenological change and the population dynamic responses emerging from it, we will need better standardization of observations (Visser & Both 2005;Miller-Rushing et al 2010), as well as funding support for long-term monitoring of a suite of ecological measures on target species.…”
Section: Discussionmentioning
confidence: 99%
“…In both the bay checkerspot and the winter moth, difficulty in documenting long-term changes in phenological synchrony stems partly from successive groups of researchers having recorded information on phenologies, fitnesses, and so on in different ways that are not strictly comparable. In order to properly record both phenological change and the population dynamic responses emerging from it, we will need better standardization of observations (Visser & Both 2005;Miller-Rushing et al 2010), as well as funding support for long-term monitoring of a suite of ecological measures on target species.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that 'mismatched' species or individuals can often switch to other food sources or move elsewhere. As discussed by Miller-Rushing et al (2010), the population biology of phenology is an area where much work remains to be done.…”
Section: Future Directionsmentioning
confidence: 99%
“…In practice, however, there are still few examples of such shifts having detectable demographic consequences. Reasons for this persistent gap, and possible solutions, are discussed by Miller-Rushing et al (2010). A convincing demonstration requires showing that a change in interaction strength or frequency has occurred, that this change is the result of climate change and that the change has altered the vital rates of one or more of the species involved.…”
Section: Ecological Effects Of Phenologymentioning
confidence: 99%
“…plants, herbivores and predators). The last point is important because, for endotherms inhabiting the tundra, it has been suggested that the most severe impact of climate warming may be indirect, through alterations in trophic interactions such as change in food availability, predation pressure, apparition of new competitors or mismatch between trophic levels [25][26][27]. Therefore, a food web approach is essential in order to fully understand the impact of climate warming on individual species [28].…”
Section: Introductionmentioning
confidence: 99%